The Effect Of Light And Shelter Period On Growth And Survival Rate Baung Fish Larvae (Hemabargus nemurus) - Miswaruddin harahap; Hamdan Alawi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT His research was conducted for 40 days from October 25, 2017 to 3 December 2017 which took place at the Laboratory of Fish Breeding and Breeding at the Faculty of Fisheries and Marine Sciences, University of Riau. This study aims to determine the Effect of Light and Shelter Interaction on the Growth and Survival of Baung Larvae (Hemabargus nemurus) which is maintained by a water aeration system. The method used in this study is the experimental method while the factorial design is Completely Randomized Design with two factors, namely the light factor with three levels of each light 0, light 12 hours, light 24 hours. Whereas the second factor is the amount of shelter provision, each S (using shelter) and NS (do not use shelter) To reduce the error of each treatment level, repeat 3 times. From the results of the study obtained the best growth and survival of G0NS (dark for 24 hours not using shelter) resulted in the growth of absolute weight of baung fish larvae of 2.44 grams, absolute growth rate of 4.91 cm followed by a specific growth rate of 11.30% / day and survival 98.92%. The results of measurements of water quality obtained temperatures ranging from 25.4-28.2 0C, pH ranged from 5.2 to 6.4 and DO ranged from 5.0 to 6.0 ppm. Keywords: Hemabargus nemurus, Light, Shelter,